Meiotic DNA Repair in the Nucleolus Employs a Nonhomologous End-Joining Mechanism. Issue 9 (2nd July 2019) - Sims, Jason; Copenhaver, Gregory P.; Schlögelhofer, Peter
Abstract : The rDNA is repaired via NHEJ during meiosis while being protected from canonical meiotic DSB formation and homologous recombination. Abstract: Ribosomal RNA genes are arranged in large arrays with hundreds of rDNA units in tandem. These highly repetitive DNA elements pose a risk to genome stability since they can undergo nonallelic exchanges. During meiosis, DNA double-strand breaks (DSBs) are induced as part of the regular program to generate gametes. Meiotic DSBs initiate homologous recombination (HR), which subsequently ensures genetic exchange and chromosome disjunction. In Arabidopsis ( Arabidopsis thaliana ), we demonstrate that all 45S rDNA arrays become transcriptionally active and are recruited into the nucleolus early in meiosis. This shields the rDNA from acquiring canonical meiotic chromatin modifications and meiotic cohesin and allows only very limited meiosis-specific DSB formation. DNA lesions within the rDNA arrays are repaired in an RAD51-independent but LIG4-dependent manner, establishing that nonhomologous end-joining maintains rDNA integrity during meiosis. Utilizing ectopically integrated rDNA repeats, we validate our findings and demonstrate that the rDNA constitutes an HR-refractory genome environment.